STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DASAR DALAM MENGGERAKAN PARTISIPASI MASYARAKAT DI KOTA JAMBI - Yoga Pratama; Yantoro; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the transformational leadership strategies of elementary school principals in mobilizing community participation in three public elementary schools in Jambi City: SDN 64/IV, SDN 54/IV, and SDN 42/IV. A qualitative case study design was employed to explore the planning, implementation, and evaluation processes based on the four dimensions of transformational leadership proposed by Bass & Avolio: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The findings show that in all three schools, principals successfully established strong partnerships with the community through vision-based planning, innovative and context-responsive program implementation, and participatory evaluation involving all stakeholders. These strategies enhanced community support in moral, material, and manpower forms, creating a more conducive and accountable school environment. The study concludes that transformational leadership effectively strengthens school– community collaboration and improves educational quality at the elementary level.